Implementation of Cryptography using the Rivest Cipher (RC4) Algorithm on QR Code Security for E-Locker Verification - Abang Muhammad Sayudi Hamzah; Uray Ristian; Kasliono (Jurnal Media Informasi Teknologi, 2026)
The Internet of Things (IoT) based E-Locker system with QR Code authentication offers ease of access, but is vulnerable to threats to the security of Universally Unique Identifier (UUID) data on locker access. This study aims to implement cryptography with the Rivest Cipher 4 (RC4) algorithm to secure UUID data on the server and determine the authentication time on the QR Code barcode to the ESP32-CAM. The RC4 algorithm uses a static key for the user. The encryption process is carried out by the Mobile with the KSA, PGRA and Base64 processes to produce ciphertext. The decryption process is carried out by the server through the Base64, KSA and PGRA processes to produce Plaintext. The test results on the RC4 UUID algorithm stored in the database are sent to the Mobile for encryption and decryption processes where QR Code authentication to the ESP32-CAM sends data to the server for data validation if successful it sends back a notification to the Buzzer once, if it fails it sounds twice. The results of the security test, sniffing was successful using the original UUID data converted to a QR Code barcode and the QR Code was authenticated to the ESP32-CAM so that it produced 2 sounds on the buzzer so that the locker access failed. The data used for authentication was 40 data from each user authenticated 10 times, with the lowest authentication time of 2.83 seconds, the longest authentication time of 12.41 seconds, and an average time of 5.42 seconds.